Islamic Ruling to Abort the Pregnancy Adultery - Hassan Khader (My University, 2014)
The research treats the issue of illegitimate pregnancy, an issue which has continued to be relevant despite the severe punishments, the serious damage and the bitterness involved. To remedy the situation, illegitimate pregnancy is often faced by the action of putting an end to the woman’s life. The woman herself often seeks abortion to hide the truth and protect her honor, or to avoid punishment. She is driven to such actions by a feeling of guilt and a fear of scandal. Such feelings reveal an instinctual admission to the graveness and ugliness of the act and its consequences, an act forbidden by all creeds and detested by rational selves and the human taste.  This being the case, some authors have argued in favor of aborting the illegitimate fetus in the interest of the woman and her family, thus overlooking the Share’a ruling on the issue. To refute such a legitimizing position the research explains Islamic rulings on fornication and illegitimate pregnancy by citing evidence from the sources of legislation using deductive and interpretive methods.

يعالج هذا البحث قضية قديمة حديثة لم تنته رغم قسوة العقوبة، وشدة الأذى، ومرارة الآثار، ولن تنتهي من المجتمعات البشرية إلى أن يقضي الله أمراً كان مفعولاً، إنها قضية حمل الزنى وما قد ينجر إثره من تصرفات، وتعمد كثير من الجهات إلى التخلص منه ومن تبعاته بقتل الزانية، وقد تلجأ هي لإسقاط حملها إخفاء لحقيقة ما كان منها، بدعوى التستر، وحفظ الأعراض، وتجنيباً لها من أن يوضع حد لحياتها، دافعها إلى ذلك الشعور بالذنب، وخشية افتضاح الأمر، وانكشاف الحقيقة، إنه شعور ينبئ عن اعتراف فطري داخلي بهول الفاحشة، وسوء عاقبتها، وقبح تلك الفعلة التي لم تبح في ملة، ولم تستطبها النفوس الأبية، ولا العقول السليمة، ولا الذوق الإنساني. قد يكون ذلك داعياً بعض الناس للجنوح إلى القول بجواز التخلص من ذلك الحمل غير المعترف به شرعاً ولا خلقاً، حفظاً لمصلحة الزانية وأهلها، ناسين أو متناسين حكم ذلك الفعل من الناحية الشرعية، فأحببت أن أبين في هذا البحث الحكم الشرعي لإسقاط الحمل من الزنى، مستنداً في ذلك إلى الأدلة الشرعية، ومناقشاً حجة الجانحين إلى الجواز، ثم رددت عليها، مراعياً مقاصد الشريعة، وقواعد الاستنباط، سائلاً الله تعالى أن أكون قد وفقت في عملي.
الحكم الشرعي لإجهاض حمل الزنى